Lactobacillus species and Clamydia trachomatis characterisation in premature rupture of membranes and normal pregnancy - Prima Indra; Roza Sri Yanti; Putra, Andani Eka (Andalas Obstetrics And Gynecology Journal, 2025)
The cause of premature rupture of membranes (PROM) remains uncertain. The vaginal microbiota might possess a significant influence on the vaginal environment and can impact the overall health of the female reproductive system. Objective: This study aims to determine the difference in the concentration of lactobacillus crispatus, lactobacillus vaginalis, and chlamydia trachomatis between patients with premature rupture of membranes and normal pregnancies; Methods: This study is an analytic study with a case-control design that was conducted at Dr. M. Djamil Hospital Padang during the period January 2024 to June 2024. This study performed DNA isolation using conventional PCR; Results: Lactobacillus crispatus, Lactobacillus vaginalis, and Chlamydia trachomatis reached 42,124,873.86/mL, 179.41/mL, and 287,062.30/mL, respectively in preterm rupture of membranes patients. In normal pregnancy, Lactobacillus crispatus, Lactobacillus vaginalis, and Chlamydia trachomatis reached 75,717,348.80/mL, 704,147.66/mL, and 0/mL, respectively. A significant difference in Lactobacillus vaginalis concentrations was found between the case and control groups, with the control group having a greater average concentration (28.88) compared to the case group (36.13), with a p-value <0.018. The case group had a significantly greater concentration of Chlamydia trachomatis (37.50) compared to the control group (27.50), with a p-value <0.001. The case and control groups had significantly different lactobacillus crispatus concentrations. The case group had 24.88 times less lactobacillus crispatus than the control group, which had 40.13 times more, with p-value <0.001; Conclusion:  In pregnant women, an increase in Chlamydia trachomatis and a reduction in Lactobacillus crispatus and Lactobacillus vaginalis can be an indicator of probable PROM. Keywords:  Lactobacillus vaginalis, chlamydia trachomatis, Lactobacillus crispatus, PROM, normal pregnancy.